Global value chain participation and exchange rate pass-through - Georgios Georgiadis; Johannes Gräb; Makram Khalil (European Central Bank (ECB), 2019)
This paper draws a causal link between the rise of global value chain participation and the decline of exchange rate pass-through to import prices over the last decades. We first present a structural two-country model in order to illustrate how participation in global value chains can impact exchange rate pass-through to import prices. In the model, the sensitivity of an economy's domestic-currency production costs to exchange rate changes rises as it participates more in global value chains by importing a larger share of its intermediate inputs. The increased sensitivity of the economy's domestic-currency production costs to exchange rate changes translates into a higher sensitivity of its domestic-currency export prices. The latter implies a reduction of the sensitivity of the economy's foreign-currency export prices | i.e. its trading partner's local-currency import prices | to exchange rate changes. Hence, an increase in the economy's global value chain participation implies a fall in its trading partner's exchange rate pass-through to import prices. We then provide empirical evidence in a cross-country panel dataset for the time period from 1995 to 2014 that is consistent with the mechanisms spelled out in the structural model. In particular, the data suggest that exchange rate pass-though to export prices is higher in economies which participate more in global value chains, and that exchange rate pass-though to import prices is lower in economies whose trading partners participate more in global value chains. Quantitatively, our estimates imply that the rise in global value chain participation can account for about 50% of the decline in exchange rate pass-through to import prices since the mid-1990s.
Keywords: F32; F41; F62; 330; Global value chain participation; exchange rate pass-through